Serum paraoxonase-1 activity as a novel marker in the diagnosis and prognosis of hyperthyroidism - Kale, Bhagwat (International Journal of Biological Research, 2013)
Thyrotoxicosis or hyperthyroidism is the clinical syndrome caused by an excess of circulating free thyroxine and free triiodothyronine, or both. It was first diagnosed in 1979 in the US. Since this time, the frequency of this diagnosis has increased. It is common, affecting about 2% of women and 0.2% of men. The most common causes of Thyrotoxicosis are Graves' disease and formation of multinodular goiter and autonomously functioning solitary thyroid nodule. In excessive production of thyroid hormones, the basal metabolic rate can be increased by 100%. Hyperthyroidism also induces a hyperdynamic cardiovascular state that is associated with tachycardia, systolic hypertension, atrial fibrillation and increased cardiovascular mortality. The present study was designed to investigate the relationship among the serum PON-1 activity, lipid profile, and thyroid hormone level in patients with hyperthyroidism. In our research, we have estimated PON 1 activity in hyperthyroidism. We found the PON 1 activity decreased in the hyperthyroid patients (144.89 ± 3.27 U/ml) as compared to controls (214.71 ± 5.46 U/ml) significantly (p < 0.05). The thyroid hormones T3 and T4 also significantly increases (p < 0.001) in hyperthyroidism. In case of lipid profile triacylglycerol, HDL cholesterol, LDL cholesterol as well as VLDL cholesterol was also found significantly decreased (p < 0.05) in hyperthyroidism. In our study, we found a decrease in triacylglycerol, HDL cholesterol, LDL cholesterol as well as VLDL cholesterol. However, the decrease in HDL, LDL and VLDL cholesterol may also be associated with other disorders. Further, the blood quantity required for lipid profile is large (5 ml) and patients have to be fast for at least 14 hours. Similarly, estimation of lipid profile is time consuming method and hence it is not preferable as a marker. The increase in thyroid hormones T3 and T4 significantly correlates with hyperthyroidism. However, estimation of thyroid hormone also required large (5 ml) quantity of blood sample. Similarly, the sample required should be always fresh. The estimation is carried generally by enzyme linked immune sorbent assay (ELISA) which is time consuming and costly method. But, on the other hand quantity of blood sample required for estimation of PON 1 activity is very less (1 ml). The estimation of PON 1 activity is easy and the method is chief. The most important thing is that PON 1 activity is decreased only in few disorders. Further, it correlates well with severity of hyperthyroidism. Thus, PON 1 activity is a novel marker in the diagnosis and prognosis of hyperthyroidism.